Results of Kidney Transplantation from Expanded Criteria Donors: A Single-Center Experience - B Palkoci; M Vojtko; J Fialov; D Osinov; M Laj?iakov (International Journal of Organ Transplantation Medicine, 2018)
Background: Collection of kidneys from extended criteria donors (ECD) with diagnosed brain-death forms a part of the collection program that increases the number of transplantations.